Study and Practice [from Learn/Destroy/Preserve, detail]. - Kitirattragarn, Victoria. (Tufts University. Tisch Library., 2019)
Installation view from Liminal Space: 2019 SMFA Senior Thesis Exhibition. Thesis project statement: How do you conserve/preserve a piece of work that is meant to be used?